Converting spent carbon cathode (SCC) into SCC-2600@rGO for superior Li+ storage performance. (April 2022) - Yang, Kai; Meng, Bicheng; Cheng, Hao; Li, Yifan; Fang, Zhao; Tian, Zhongliang; Lai, Yanqing
Abstract: Exploiting the characteristics of carbonaceous solid waste for added-value applications is a potential strategy for realizing resource recycling and reducing pollution. Graphitized spent carbon cathode (SCC) used as negative electrodes in lithium-ion batteries exhibits unacceptable high-rate cycle performance. In this study, the effect of the heating rate on the microstructure and electrochemical properties of SCC-2600@rGO fabricated by the self-cycling combined with interfacial assembly was investigated. SCC-2600@rGO-8 has the abundant defects, appropriate content of oxygen functional groups, hierarchical pore structure, and complex graphene conductive network. And the unique microstructures can provide numerous active sites for lithium storage, accelerate the charge transfer rate, and maintain structural stability. As a consequence of these features, SCC-2600@rGO-8 anodes have the attractive electrochemical properties, including a high charge capacity (753.1 mAh/g at 0.1 C after 50 cycles) and a notable rate capability (614.9 mAh/g at 1 C after 500 cycles and 278.0 mAh/g at 5 C after 2500 cycles). Graphical abstract: Image 1 Highlights: Surface engineering makes the stability and cyclic properties of SCC-2600 obviously improve. The heating rate of the assembled SCC-2600@rGO is optimized. SCC-2600@rGO-8 anodes show 614.9 mAh·g −1 at 1C after 500 cycles. It provides a reference for the value-added utilization of carbonaceous solid waste.